2007
DOI: 10.1002/ajmg.a.31591
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of holoprosencephaly–diencephalic hamartoblastoma (HDH) association

Abstract: We report on a 23-week fetus with a hypothalamic hamartoma, lobar holoprosencephaly, right anophthalmia, and facial asymmetry, features which are consistent with the holoprosencephaly-diencephalic hamartoblastoma (HDH) association. In an attempt to better delineate HDH, we reviewed 19 published patients with similar features. The HDH clinical spectrum ranges from classic holoprosencephaly with micro/anophthalmia, multiple additional findings in non-contiguous structures and early lethality, to isolated microfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
(80 reference statements)
2
9
0
Order By: Relevance
“…This work offered a detailed description of five 19‐ to 28‐week‐old fetuses with large hypothalamic/diencephalic hamartomas and other cephalic anomalies, primarily midline defects and severe facial asymmetry. The manuscript supported the concept that the hypothalamic mass caused additional brain and craniofacial malformations, particularly of the holoprosencephaly/arrhinencephaly type, in a sequential model [Iafolla et al, 1989; Verloes et al, 1992; Castori et al, 2007a]. Herein, I offer further speculations on this rare phenomenon.…”
Section: To the Editorsupporting
confidence: 63%
See 4 more Smart Citations
“…This work offered a detailed description of five 19‐ to 28‐week‐old fetuses with large hypothalamic/diencephalic hamartomas and other cephalic anomalies, primarily midline defects and severe facial asymmetry. The manuscript supported the concept that the hypothalamic mass caused additional brain and craniofacial malformations, particularly of the holoprosencephaly/arrhinencephaly type, in a sequential model [Iafolla et al, 1989; Verloes et al, 1992; Castori et al, 2007a]. Herein, I offer further speculations on this rare phenomenon.…”
Section: To the Editorsupporting
confidence: 63%
“…It has become clear that arrhinencephaly/holoprosencephaly is not the sole cephalic anomaly associated with HDH. In fact, hemifacial microsomia variably combined with an ipsilateral malformed ear and cervical and/or upper thoracic costo‐vertebral anomalies was observed in the five patients reported by Guimiot et al 2009 and six additional, previously reported cases [reviewed in Castori et al, 2007a]. This is similar to Goldenhar syndrome, which is a causally heterogeneous malformation apparently reflecting perturbed migration and/or differentiation of the cephalic neural crest [Cohen et al, 1989].…”
Section: To the Editormentioning
confidence: 91%
See 3 more Smart Citations